2016
DOI: 10.1159/000445464
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Testicular Disorder of Sex Development in a Dog (78,XX; <b><i>SRY</i></b>-Negative) with Male External Genitalia and Detection of Copy Number Variation in the Region Upstream of the <b><i>SOX9</i></b> Gene

Abstract: Testicular or ovotesticular disorder of sex development (DSD) in genetic females (78,XX; SRY-negative) has been reported quite frequently in numerous dog breeds and is usually diagnosed due to the presence of female external genitalia with an enlarged clitoris. The molecular background of this disorder, diagnosed also in human and other mammals, is not fully understood. However, it has recently been proposed that a copy number variation (CNV) in the region upstream of the SOX9 gene is associated with it. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
4
15
0
Order By: Relevance
“…Therefore, we can assume the presence of functional testicles, at least for the production of the necessary hormones for the development of a penis. This condition was recently reported in a dog [Szczerbal et al, 2016].…”
Section: Resultssupporting
confidence: 62%
“…Therefore, we can assume the presence of functional testicles, at least for the production of the necessary hormones for the development of a penis. This condition was recently reported in a dog [Szczerbal et al, 2016].…”
Section: Resultssupporting
confidence: 62%
“…DNA from blood samples was isolated using Blood Mini and Genomic Mini kits (A&A Biotechnology), respectively. The presence of the sex chromosome-linked genes ( SRY, ZFY, and ZFX ) was detected using PCR and RFLP techniques as described earlier [Switonski et al, 2012;Szczerbal et al, 2016].…”
Section: Pcr Detection Of Sex Chromosome-linked Genesmentioning
confidence: 99%
“…For the first time in literature, they clearly showed that two of them carried SOX9 gene duplication. Recently, Szczerbal et al () have observed a distinct size variation in the copy number variation (CNV) region upstream of the SOX9 gene in a French bulldog with abdominal testes and male external genitalia. The dog manifested as a female karyotype (78, XX; SRY ‐negative) with no translocation involving the Y chromosome.…”
Section: Discussionmentioning
confidence: 99%